THE PSYCHOLOGICAL EFFECT OF AN ABUSIVE RELATIONSHIP IN THE FAMILY ON THE FORMATION OF PERSONALITY - Imonova , Мафтуна (Eurasian Journal of Academic Research, 2024)
This article discusses violence in family relationships, violation of personal boundaries between spouses, humiliation of human personality, and the impact of cruel treatment on children's character.